Acute upper gastrointestinal bleeding: a guide for nurses. (10th January 2019) - Chapman, Warren; Siau, Keith; Thomas, Fiona; Ernest, Selvajothi; Begum, Shriya; Iqbal, Tariq; Bhala, Neeraj
Abstract : This article outlines latest evidence-based care for patients with acute upper gastrointestinal (GI) bleeding. It aims to help gastroenterology and general medical ward nurses plan nursing interventions and understand the diagnostic treatment options available. Acute upper GI bleeding can present as variceal or non-variceal bleeding and has a high death rate. Endoscopy is used for diagnosis and to provide therapy, prior to which the patient should be adequately resuscitated and assessed. Various therapies can be initiated at endoscopy, depending on the source of bleeding. If bleeding continues in spite of these therapies, further interventions such as the Sengstaken tube, oesophageal stents, radiological or surgical treatments may be required. After endoscopy, it is important to have a plan for ongoing treatment. Patients may require acid suppression treatment or eradication of Helicobacter pylori as part of their treatment plan. They may in additional require correction of their haemoglobin levels and follow-up endoscopy. It is essential that nurses caring for such patients are aware of the current UK guidance and help patients to adhere to agreed treatment plans.